KEDUDUKAN JAMINAN DAN DENDA PADA PEMBIAYAAN BANK SYARIAH - Nonie Afrianty (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2018)
Islamic banking has a role as an intermediary institution that is an intermediary between savers and investors and banks to function as an agent of development. In funds, Islamic banks must provide the requirements that must be met by the customer (debtor), one of which is the guarantee and in the event of late payment by the customer, will be fined. However, in reality there are many financing that does not run smoothly. Islamic bank collateral position is as an application of the precautionary principle and the prudential banking bank or a fine position in Islamic banks are based on the principle ta'zir which aims to enable customers to be more disciplined in carrying out its obligations. The funds raised from fines is intended for charity